Effect of galantamine on attention in patients with Alzheimer's disease combined with cerebrovascular disease. Issue 10 (9th December 2016) - Park, Jeong Jin; Choi, Seong Hye; Kim, SangYun; Lee, Ae Young; Moon, So Young; Lee, Jun Hong; Kwon, Jae Cheol; Park, Kyung Won; Ku, Bon D.; Han, Hyun Jeong; Kim, Eun‐Joo; Shim, Yong S.
Abstract : Aim: Patients with Alzheimer's disease (AD) and cerebrovascular disease (CVD) show greater attentional deficits compared with AD patients without CVD. The aim of the present study was to investigate the effect of galantamine on attention in AD patients with CVD. Methods: In this open trial, 1512 patients with AD and CVD were recruited from 71 nationwide hospitals. The patients were given galantamine for 16 weeks. The primary outcome measure was the score on the Attention Questionnaire Scale (AQS), which measures the patients' attention in their daily lives. The secondary outcome measures were the scores on the Korean Mini‐Mental State Examination, the Clinical Dementia Rating scale and the Global Deterioration Scale. Efficacy measures were calculated both at baseline and at the end of the treatment (week 16). Results: The responders rate on the AQS (change of the AQS from baseline >0) was 60.6% in AD patients with CVD. At the end of the treatment, both the AQS (15.0 ± 5.7 vs 16.3 ± 5.8, P < 0.001) and the Korean Mini‐Mental State Examination scores (17.8 ± 4.8 vs 18.1 ± 5.1, P < 0.001) showed a significant improvement relative to the baseline performance. The Clinical Dementia Rating (1.25 ± 0.59 vs 1.22 ± 0.63 P = 0.025) and Global Deterioration Scale (3.82 ± 0.94 vs 3.76 ± 0.96, P = 0.002) scores also showed a significant decrease at the end of the treatment. Conclusions: Galantamine is effective in improving attention in the daily lives of AD patients with CVD.Geriatr Gerontol Int 2017; 17: 1661–1668.